Effect of Patient Age on Management Decisions in Breast Cancer: Consensus from a National Consultation - Leonard, Robert C. (AlphaMed Press, 2010)
This qualitative study investigated the attitudes, perceptions, and practices of breast cancer specialists with reference to the effect of patient age on management decisions in breast cancer, and attempted to identify national consensus on this issue. One hundred thirty-three relevant specialists, including 75 surgeons and 43 oncologists, participated in a virtual consultation using e-mailed questionnaires and open-ended discussion documents, culminating in the development of proposed consensus statements sent to participants for validation. A strong consensus was seen in favor of incorporating minimum standards of diagnostic services, treatment, and care for older patients with breast cancer into relevant national guidance, endorsed by professional bodies. Similarly, an overwhelming majority of participants agreed that simple, evidence-based protocols or guidelines on standardizing assessment of biological and chronological age should be produced by the National Institute for Health and Clinical Excellence and the Scottish Medicines Consortium, developed in collaboration with specialist oncogeriatricians, and endorsed by professional bodies. A further recommendation that all breast cancer patient treatment and diagnostic procedures be undertaken in light of up-to-date, relevant scientific data met with majority support. This study was successful in gauging national specialist opinion regarding the effect of patient age on management decisions in breast cancer in the U.K.